Chronic occupational exposure endured by tobacco farmers from Brazil and association with DNA damage. (2nd February 2018) - Kahl, Vívian F Silva; Dhillon, Varinderpal Singh; Simon, Daniel; da Silva, Fernanda Rabaioli; Salvador, Mirian; Branco, Cátia dos Santos; Cappetta, Mónica; Martínez-López, Wilner; Thiesen, Flávia V; Dias, Johnny F; Souza, Claudia Telles de; Fenech, Michael; et al.
Abstract: Tobacco farming is an important economic income in Brazil, although it has been challenged as regard the occupational exposure to both pesticides and nicotine endured by farmers. Chronic occupational exposure to complex mixtures can lead to health hazardous. We examined genomic instability and epigenetic changes in tobacco farmers occupationally exposed to pesticide mixtures and nicotine at tobacco fields. DNA damage was assessed by alkaline comet assay in blood cells. Genomic DNA was isolated, and telomere length was measured using quantitative polymerase chain reaction assay. We measured 5-methyl-2′-deoxycytidine, a marker of global DNA methylation, and p16 promoter methylation. The oxidative profile was evaluated by trolox equivalent antioxidant capacity and lipid peroxidation (thiobarbituric acid reactive substances) in serum. Exposure parameters, plasma cotinine and inorganic element levels, were also measured. DNA damage was significantly elevated for farmers in relation to unexposed group ( P < 0.001; Mann–Whitney test) and positively associated with years of exposure. Inverse relationship between DNA damage and total equivalent antioxidant activity was demonstrated for exposed and unexposed groups. Exposed group showed significantly shorter telomeres ( P < 0.001; unpaired t -test) and DNA hypomethylation ( P < 0.001; unpaired t -test), as well as p16 hypermethylation ( P = 0.003; Mann–Whitney test). Lipid peroxidation was increased for exposed group in relation to unexposed one ( P = 0.02; Mann–Whitney test) and presented a positive correlation with global DNA methylation ( P = 0.0264). Farmers have increased plasma cotinine levels ( P < 0.001) and inorganic elements (phosphorus, sulphur and chlorine) in relation to unexposed group. Elevated oxidative stress levels due to chronic occupational pesticide mixtures and nicotine exposure in tobacco farmers were associated with higher DNA damage, shorter telomeres and altered DNA methylation. Telomere-accelerated attrition due to exposure may be potential intermediate step before a disease state.